A Real-World Study on Pulmonary Arterial Hypertension in Bulgaria: A Single-Center Retrospective Study From 2012 to 2022 - Vasil Velchev; Arman Postadzhiyan; Sarkis Kalustian; Simona Markova; Mihaela Manolova; Damyan Boychev; Daniel Penchev; Martina Nacheva; Elina Petrova (Cardiology Research and Practice)
Major Conclusions: The findings highlight the need for earlier diagnosis and more aggressive treatment strategies, as monotherapy appears insufficient for optimal outcomes in advanced PAH. Establishing a national PAH registry and increasing disease awareness could facilitate earlier interventions and improve patient outcomes in Bulgaria.